Pemberdayaan Kelompok Tani Kopi Desa Balerante Kabupaten Klaten - Lantarsih, Retno; Kresnanto, Nindyo Cahyo; Raharti, Rini; Putri, Wika Harisa (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to improve the knowledge and skills of farmer groups in handling coffee plant pests and diseases, improve financial governance, improve human resource capabilities in excellent service for visitors to Balerante coffee shops, and improve the number of coffee cultivation equipment and coffee serving equipment. The target audience of the partnership program in this community is a group of coffee farmers in Balerante village, Kemalang District, Klaten Regency. The results of the activity show that farmer groups had knowledge and skills in identifying, handling, and preventing diseases in coffee plants, farmer groups carried out more intensive care of coffee plants, and farmer groups had knowledge and skills in providing excellent service to coffee shop visitors, and farmer groups already had equipment for serving coffee in larger quantities so that it could increase the capacity of the coffee shop in Balerante village.